Antimicrobial activity of Helichrysum species and the isolation of a new phloroglucinol from Helichrysum caespititium - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2013)
Dissertation (PhD (Plant Physiology))--University of Pretoria, 2004.